TEKNIK MENYARING INFORMASI INTERNET UNTUK MENDAPATKAN MATERI BELAJAR - ADRIYENDI, ADRIYENDI (Sainstek : Jurnal Sains dan Teknologi, 2010)
A important component of teaching learning  process  is  teaching  material.    A  good  teaching  material  will  produce  optimal  and  new  (recent)  teaching  learning  process.  Internet is a source where we can find and get the new teaching recently. To find the teaching material, we have to know the computer identity where the teaching material is located. The Internet can be categories into 2 categories namely edu (education) for  computer which located in United State and ac (academic) which is followed by country  code for computer which located in the outside of United State. Filtering information with Search Engine include Power Searching Conceptual with application need technique for get information is expected. Key words: filter, information, website, teaching material, find and get